TANTANGAN FILOSOFIS PENDIDIKAN (MEMAHAMI ANCAMAN LINEARITAS PENDIDIKAN MODERN) - Ida Bagus Made Satya Wira Dananjaya; I Made Danu Tirta (Guna Widya: Jurnal Pendidikan Hindu, 2021)
Education is a conscious effort for the development of students towards their best achievement. The phrase best achievement is defined as the achievement of a person to become an expert or expert in one field. These ideals are very noble and become the concentration of policy holders in implementing the education system and seem flawless. The linearity of the education system is the answer to the government's desire to make students an expert in one field of science. The assumption of perfect linearity in education is refuted when expertise is not accompanied by qualified moral aspects and a plurality of perspectives in solving life's problems. This threat is seen when linearity in the field of education is not accompanied by a broader perspective to understand the very complex problems of life. The importance of understanding the threat of the linearity of education is the best way to foster sensitivity and diversity in solving problems of human life.